PENERAPAN INTERVENSI TERAPI MUSIK ROHANI DALAM ASUHAN KEPERAWATAN PADA LANSIA DENGAN MASALAH GANGGUAN POLA TIDUR - Lantong, Yona M. K; Lamonge, Annastasia Sintia (Lasalle Health Journal, 2023)
Introduction: Disturbed sleep pattern is one of the nursing problems that is often experienced by the elderly as a result of the aging process and diseases suffered by the elderly. Giving musil therapy is one of the evidence based on the results of previous studies which have proven to be effective in improving sleep quality. Objective: to implement evidence-based provision of spiritual music therapy as a nursing therapeutic intervention for elderly patients with sleep pattern disturbances. Method: The design used is a case study. Three cases of elderly patients with sleep disorder nursing problems were involved in this case study. Case analysis uses a qualitative approach of the nursing process, namely: assessment, data analysis and nursing diagnosis, planning, implementation and evaluation. Results: the three cases of patients had sleep pattern disturbance nursing problems. After the intervention of providing spiritual music therapy for three days, there was an improvement in the quality of sleep in two cases and the problem of nursing sleep patterns was resolved for one case. Conclusion: Providing spiritual music therapy can be a therapeutic action for nurses to improve the sleep quality of the elderly by considering the source of the cause of the sleep pattern disturbance.